Medical immunology for students - Playfair, J. H. L. (Churchil Livingstone, 1998)
Immunology is a vital discipline which permeates the whole of medicine. But all too often it is treated as an esoteric biochemical science, swamping the medical student with unnecessary information and losing sight of immunology's clinical relevance. This new title by two distinguished authors rectifies the balance, providing medical students with a solid scientific background whilst emphasising the links between immunology and other areas of the curriculum, such as physiology, genetics, pathology and microbiology. Clinical conditions are assessed system by system, allowing students to refer to the relevant section as they proceed through the medical and surgical firms. A special section is devoted to vaccination and the related epidemiological and public health considerations involved in the management of infectious disease in the population. With every four pages corresponding to a 50-minute lecture, and with material presented in convenient double page spreads with clear, simple diagrams, Immunology for Medical Students demystifies this essential subject and ensures that medical students have a firm grasp of its clinical importance. Features: * Basic and clinical immunology in one book * Highly illustrated, user-friendly layout * Concentrates on what the students need to know * Contains self-assessment questions for revision and exam preparation * Written for the new medical curriculum